Recent Progress on Perovskite Photodetectors for Narrowband Detection - Lu, Xingyu; Li, Junyu; Zhang, Yuanzhou; Han, Zeyao; He, Zeren; Zou, Yousheng; Xu, Xiaobao (Advanced photonics research, 2022)
Narrowband detection is of urgent demand in many fields, such as machine vision, biofluorescence imaging, artificial intelligence, flame, or gas molecule monitoring. However, the restricted recognition area and complex integration hinder the development of narrowband photodetectors. Due to the excellent photoconversion efficiency, metal halide perovskites are emerging as a new star in the field of high‐performance photodetectors. In recent years, soaring attention has been focused on narrowband photodetectors using perovskites as absorbing layers, owing to the excellent narrowband detection performance and tunable narrowband absorption peaks covering a wide optical range. Herein, this review is focused on the latest research progress of perovskite narrowband photodetectors, emphasizing the strategy of using perovskites for narrowband photodetectors from novel functional integration to applications and existing problems. The study is looking forward to elucidating different internal mechanisms of narrowband detection, providing unique insights into the challenges in this research area, and giving rise to the prosperity of narrowband detection. Metal halide perovskite is ideally suited for narrowband photodetectors due to its excellent optoelectronic performance and flexible adjustable bandgap. Constructed with both input optical filtering and internal filtering strategies, perovskite narrowband photodetectors offer excellent narrowband detection performance and have evolved to be lead‐free, dual‐band, and multifunctional, making them ideal for applications such as color recognition, imaging, etc.